Scaling up emotional intelligence and critical thinking of students in biology using two concept mapping strategies - Kpiranyam, Felix Sesugh; Achor, Emmanuel Edoja; Fakaa, Stanley Gbaden (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study aimed to scale up the emotional intelligence and critical thinking of students in Biology using two concept-mapping instructional strategies in Katsina-Ala Township. Two research questions and two hypotheses guided the study. A quasi-experimental design which involved two experimental groups and one control group was employed. One hundred and fourteen (114) Senior Secondary (SS) II students offering Biology out of a population of 3,537 were drawn using random sampling. Two instruments: The students' Emotional Intelligence Questionnaire (SEIQ) and the Critical Thinking Test (CTT) with reliability indexes of 0.82 and 0.87 using Cronbach Alpha and Kuder-Richardson 21 (K-R21) formulae respectively were used. Trained research assistants used the lesson plans for teaching. Mean and standard deviation aided in answering research questions and Analysis of Covariance (ANCOVA) was utilised to test hypotheses at 0.05 significant level. Significant differences existed in mean emotional intelligence ratings of students in Concept Mapping Instructional Strategy (CMIS), Peer-Collaboration Concept Mapping Instructional Strategy (PCMIS) and Conventional Instructional Method (CIM) groups (p<0.05). Post Hoc test revealed a significant difference in the mean emotional intelligence ratings between students taught using CMIS and CIM (p<0.05), PCMIS and CIM (p<0.05), but not between CMIS and PCMIS (p>0.05). Findings also revealed a significant difference in students' mean critical thinking scores among CMIS, PCMIS and CIM groups (p<0.05). Post Hoc test revealed a significant difference in the mean critical thinking scores between students taught using CMIS and CIM (p<0.05), PCMIS and CIM (p<0.05), but not between CMIS and PCMIS (p>0.05). Hence it was recommended that teachers should use PCMIS strategies to improve students’ emotional intelligence and critical thinking in Biology